PELATIHAN PEMBUATAN WEBSITE BERBASIS CMS WORDPRESS DI PUSAT KEGIATAN BELAJAR MASYARAKAT SEKOLAH BINTANG - Shela, Shela; Krisvyanti, Fanny; Robert, Michael Roda; Robert, Victoria Valensita; Andreyas, Andreyas; Sewithto, Muhyi Haadi; Udjulawa, Daniel (FORDICATE, 2025)
Abstract: Effective information management and improved access to educational programs remain key challenges for non-formal educational institutions such as PKBM Sekolah Bintang. To address these issues, this community service activity was designed to enhance the digital skills of PKBM administrators through training in the creation and management of a CMS-based WordPress website. The training was conducted in an interactive and practical manner, with PKBM students as the main participants. Evaluation results indicated a significant improvement in participants’ ability to independently manage the website, from installation and design customization to digital content management. The website now serves as an effective communication and promotional tool to broaden the reach of the institution’s educational programs. However, continued training and technical support are still needed to optimize website management and ensure the sustainability of the institution’s digital capacity. Overall, this initiative contributes significantly to strengthening the use of information technology in non-formal education. Abstrak: Pengelolaan informasi yang efektif serta peningkatan akses terhadap program pendidikan menjadi tantangan utama bagi lembaga pendidikan non-formal seperti PKBM Sekolah Bintang. Untuk mengatasi hal ini, kegiatan pengabdian masyarakat ini dirancang guna meningkatkan kemampuan digital siswa PKBM melalui pelatihan pembuatan dan pengelolaan website berbasis CMS WordPress. Pelatihan yang berlangsung secara interaktif dan praktis melibatkan murid PKBM sebagai peserta utama. Evaluasi hasil pelatihan menunjukkan adanya peningkatan kemampuan peserta dalam mengelola website secara mandiri, mulai dari instalasi, pengaturan tampilan, hingga pengelolaan konten digital. Saat ini, website tersebut berfungsi sebagai media komunikasi dan promosi yang efektif untuk memperluas jangkauan informasi program pendidikan kesetaraan. Meski demikian, pelatihan lanjutan serta pendampingan teknis tetap diperlukan guna mengoptimalkan pengelolaan website dan mendukung keberlanjutan peningkatan kapasitas digital lembaga. Secara keseluruhan, kegiatan ini memberikan kontribusi penting dalam memperkuat pemanfaatan teknologi informasi pada pendidikan non-formal.